Dual and selective inhibitors of pteridine reductase 1 (PTR1) and dihydrofolate reductase-thymidylate synthase (DHFR-TS) from Leishmania chagasi. (1st January 2019) - Teixeira, Bárbara Velame Ferreira; Teles, André Lacerda Braga; Silva, Suellen Gonçalves da; Brito, Camila Carane Bitencourt; Freitas, Humberto Fonseca de; Pires, Acássia Benjamim Leal; Froes, Thamires Quadros; Castilho, Marcelo Santos
Abstract: Leishmaniasis is a tropical disease found in more than 90 countries. The drugs available to treat this disease have nonspecific action and high toxicity. In order to develop novel therapeutic alternatives to fight this ailment, pteridine reductase 1 (PTR1) and dihydrofolate reductase-thymidylate synthase (DHF-TS) have been targeted, once Leishmania is auxotrophic for folates. Although PTR1 and DHFR-TS from other protozoan parasites have been studied, their homologs in Leishmania chagasi have been poorly characterized. Hence, this work describes the optimal conditions to express the recombinant Lc PTR1 and Lc DHFR-TS enzymes, as well as balanced assay conditions for screening. Last but not the least, we show that 2, 4 diaminopyrimidine derivatives are low-micromolar competitive inhibitors of both enzymes ( Lc PTR1 Ki = 1.50–2.30 µM and Lc DHFR Ki = 0.28–3.00 µM) with poor selectivity index. On the other hand, compound 5 (2, 4-diaminoquinazoline derivative) is a selective Lc PTR1 inhibitor (Ki = 0.47 µM, selectivity index = 20).